2017
DOI: 10.1093/cvr/cvw234
|View full text |Cite|
|
Sign up to set email alerts
|

Multilevel analyses of SCN5A mutations in arrhythmogenic right ventricular dysplasia/cardiomyopathy suggest non-canonical mechanisms for disease pathogenesis

Abstract: Almost 2% of ARVD/C patients harbour rare SCN5A variants. For one of these variants, we demonstrated reduced sodium current, Na1.5 and N-Cadherin clusters at junctional sites. This suggests that Na1.5 is in a functional complex with adhesion molecules, and reveals potential non-canonical mechanisms by which Na1.5 dysfunction causes cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 30 publications
2
120
0
1
Order By: Relevance
“…Recent studies have suggested that mutations in SCN5A may account for a small portion of the ARVC phenotype cohorts 31. This is consistent with multiple studies that have demonstrated that desmosomal proteins are associated with altered kinetics of the sodium current in cardiomyocytes,32 a manifestation that precedes structural abnormalities, as seen in a DSG2 mouse model 33.…”
Section: Introductionsupporting
confidence: 82%
“…Recent studies have suggested that mutations in SCN5A may account for a small portion of the ARVC phenotype cohorts 31. This is consistent with multiple studies that have demonstrated that desmosomal proteins are associated with altered kinetics of the sodium current in cardiomyocytes,32 a manifestation that precedes structural abnormalities, as seen in a DSG2 mouse model 33.…”
Section: Introductionsupporting
confidence: 82%
“…PLN has been identified as a causative factor in a significant portion of individuals with ARVC patients 3, 6. Additionally, recent reports have identified SCN5A mutations in a small percentage of ARVC patients 7. Overlap between ARVC and dilated cardiomyopathy has been well described, and pathogenic variants in sarcomere genes have been associated with DCM 8.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular genetic testing revealed a rare SCN5A variant. SCN5A variants have been associated with ARVC in 2% of cases [32]. Renewed clinical evaluation of the proband revealed a high burden of atrial and ventricular premature contractions, and cascade screening revealed multiple affected family members (Supplementary Material, page 13).…”
Section: Discussionmentioning
confidence: 99%